Injuries among middle aged and older adult patients presenting to the emergency department: a retrospective cohort study - Basnawi, Abdullah M.; Hashim, Syeda Nafeesa; Khan, Sariya; Irfan Thalib, Husna; Ayub, Ayesha Mirza; Hashim, Sana; Shakeel, Fatimah; Timraz, Jumana; Islam, Fathma (Frontiers in Aging, 2025)
IntroductionAs the global population ages, trauma among middle aged and older adults has become a significant public health concern, particularly in emergency care settings. In Saudi Arabia, the number of adults aged ≥50 years is steadily increasing, particularly in urban centers such as Jeddah, where multigenerational households and chronic health conditions influence injury patterns and healthcare utilization. Middle aged and older adults face higher rates of injury-related hospitalizations than younger populations, often exacerbated by physiological vulnerability and comorbid conditions. This retrospective study aimed to evaluate the sociodemographic factors, prevalent injury types, associated comorbidities, and clinical outcomes of middle aged and older adult’s patients presenting to the emergency department (ED) with trauma.MethodsA retrospective cohort study was conducted on patients aged ≥50 years who presented to the ED with trauma between January 2021 and December 2023. The assessed variables included sociodemographic data, injury severity, injury patterns, comorbidities, clinical management, and outcomes. Statistical analysis was performed using chi-square tests and logistic regression to identify the associations and predictors of surgical intervention.ResultsA total of 248 middle aged and older adult patients with trauma were analyzed. Male patients sustained more severe injuries, with a statistically significant association between gender and injury severity (p = 0.028). No significant correlation was found between injury severity, age, and comorbidities. Logistic regression revealed that the mode of arrival and lower body injuries were significant predictors of surgical intervention (OR = 2.714, p = 0.046). Patients arriving by walk-in (OR = 7.560, p = 0.002) or personal vehicle (OR = 5.231, p = 0.006) were more likely to undergo surgery than those transported by ambulance. Surgical intervention was inversely associated with injury recurrence (OR = 0.214, p = 0.019), whereas the presence of comorbidities significantly increased the likelihood of surgical management (OR = 2.024, p = 0.031).ConclusionMiddle aged and Older adult trauma patients represent a complex and vulnerable population in emergency care. Male gender, lower limb injuries, comorbidities, and non-ambulance transport modes are significant predictors of surgical intervention. Identifying these factors can guide early triage, optimize care, and inform preventive strategies to improve outcomes and reduce the healthcare burden.